Evaluation of the Level of Salivary sHLA-G in Children Aged 3–5 Years with or without Dental Caries - Mansoureh Bijani; Amrollah Mostafazadeh; Mina Motallebnejad; Ali Bijani; Roghiyeh Pourbagher; Samaneh Gharekhani (International Journal of Dentistry)
Aim and Background. Early childhood caries (ECC) is a common type of dental caries affecting children. As dental caries is a bacterial infectious disease, the host immune system parameters including soluble human leukocyte antigen-G (sHLA-G) are essential factors in estimating dental caries. The study aimed to investigate and compare the concentration of sHLA-G in the saliva of children with or without dental caries. Methods and Materials. This analytic cross-sectional study was carried out on 83 healthy children aged 3 to 5 years of both genders, who were divided into three groups based on decayed dental surfaces (ds): group 1, caries-free children (CF, n = 29); group 2, children with 1 ≤ ds ≤ 3, 1 ≤ ds ≤ 4, and 1 ≤ ds ≤ 5 for age 3, 4, and 5 years, respectively (ECC, n = 20); and group 3, children with ds ≥ 4, ds ≥ 5, and ds ≥ 6 for age 3, 4, and 5 years, respectively (S-ECC, n = 34). The unstimulated saliva samples were collected, and the salivary sHLA-G concentration was measured by the ELISA kit. The SPSS Statistics v17.0 software and Mann–Whitney, Kruskal–Wallis, chi-square, and Spearman’s rank correlation tests were used for statistical analysis. The level of significance was considered at p<0.05. Results. The mean concentrations of salivary sHLA-G in CF, ECC, and S-ECC groups were 3.18 ± 2.28, 5.64 ± 5.51, and 6.21 ± 6.03 ng/l, respectively (p=0.047), and the mean salivary sHLA-G level was comparatively higher in children with dental caries than that of the CF group (p=0.02), but there is no significant difference between ECC and S-ECC groups (p>0.05). Spearman’s rank correlation test showed a weak positive correlation (p=0.039, r = 0.22), between the level of salivary sHLA-G and dental caries. Conclusion. The present study provides some preliminary evidences on relationship between sHLA-G and dental caries in children.